Anteseden Keputusan Konsumen dalam Membeli Produk Mi Instan Sehat dengan Brand Ambassador Artis Korea - Adinda Puspita Sari; Usep Suhud; Daru Putri Kusumaningtyas; Rahmi Rahmi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to test the antecedents of consumer decisions in purchasing healthy instant noodle products with Korean artist brand ambassadors. Consisting of five variables used, namely product quality, price perception, brand ambassador, purchase intention, and purchase decision. The influence of product quality, price perception, and brand ambassador on purchase intention. As wel as testing the influence of product quality, price perception, and brand ambassador on purchase decisions. This research was conducted in the DKI Jakarta area. The approach used in this study is a quantitative approach using a survey method by distributing questionnaires online through social media. The population used in this study were consumers who knew and had consumed Mi Lemonilo products with NCT Dream as brand ambassador, domiciled in DKI Jakarta, and were at least 17 years old. This study used a purposive sampling technique, with a total sample of 215 respondents. The data analysis technique in this study used SEM (Structural Equation Modeling) with AMOS (Analysis of Moment Structure) software. The results showed that product quality and price perception had a positive and significant effect on purchase intention. However, brand ambassador did not have a significant effect on purchase intention. Furthermore, product quality and brand ambassador had a positive and significant effect on purchase decision. Meanwhile, price perception did not affect purchase decision. Purchase intention had a positive and significant effect on purchase decision.